THE SYNTHESIS OF POLYHYDROXYLATED AMINO-ACIDS FROM GLUCURONOLACTONE - ENANTIOSPECIFIC SYNTHESES OF 2S,3R,4R,5S-TRIHYDROXYPIPECOLIC ACID, 2R,3R,4R,5S-TRIHYDROXYPIPECOLIC ACID AND 2R,3R,4R-DIHYDROXYPROLINE - Bashyal, B; Chow, H; Fellows, L; Fleet, G (1987)
The potential of D-glucuronolactone for the synthesis of polyhydroxylated amino acids is illustrated by the enantiospecific syntheses of 2S,3R,4R,5S-trihydroxy-pipecolic acid, 2R, 3R, 4R, 5S-trihydroxypipecolic acid and 2R,3R,4R-dihydroxyproline. © 1987.